PEKAN KEBUDAYAAN ACEH DALAM PERSPEKTIF HISTORIS - Septian Fatianda; Nuraini A. Manan; Muhammad Yunus Ahmad (Indonesian Journal of Islamic History and Culture, 2020)
This article is entitled Pekan Kebudayaan Aceh (Aceh Cultural Week) in Historical Perspective. Aceh Cultural Week or PKA is a cultural event displaying cultural richness through cultural attractions, artistic performances, exhibitions and cultural seminars. The purpose of this research is to find out the early history of PKA implementation and its development, impact, shifting in the initial PKA values and objectives, as well as criticism and input on the implementation of PKA. This study uses the historical method through heuristic steps, interviews, source criticism, interpretation, and historiography or history writing. The results of this study explain that the Aceh Cultural Week has been implemented for seven times where firstly held was in 1958 and continued until the latest (seventh) PKA in 2018. This PKA is aimed to develop and preserve Aceh's historical, traditional and cultural values and as a means of unifying various ethnic groups in Aceh. In addition, PKA has provided substantial results for the preservation of Aceh's culture. Furthermore, this research also explains that the society highly appreciates the implementation of PKA despite some points that need to be evaluated in order to achieve the noble ideals of PKA itself.